Recombination of asphalt with bio-asphalt : binder formulation and asphalt mixes application - Peralta, J. (2014)
The bio-oil from fast pyrolysis is mainly produced using organic waste materials. This is a viscoelastic material, and after a heat treatment it has a viscosity and high/intermediate thermal rheological behavior similar to many types of asphalt used in the paving industry. These two characteristics show that this material could be a good alternative to replace asphalt. In order to improve the performance of bio-oil, it was hypothesized that the addition of crumb rubber would change the rheology of the modified bio-oil, making it rheologically similar to the conventional paving asphalts. Therefore, two sources of ground rubber from used tires (GTR), from different manufacturing processes, were used to modify the bio-oil. Then, two blends were produced by adding 20% (w/w) of this bio-binder to two different asphalts, a PG58-28 and a PG64-22. The binders were aged, and then storage stability tests (separation sensibility) were performed. The rheology of the initial bio-oil, bio-binder, asphalts and resulting binder-blends were assessed by using a Dynamic Shear Rheometer (DSR), namely by performing frequency sweeps at different temperatures. The results were then used to build the master curves of the materials, and to determine their high temperature continuous performance grade. Additionally, the performance related behavior of mixtures produced with this new material was also assessed, in order to evaluate the advantages of its use in pavements. Therefore, two mixes were produced with the binder that showed better performance regarding thermal rheological behavior, aging susceptibility and separation tendency. These new mixes were finally studied using performance related tests that are able to estimate their future behavior in situ in different environmental and traffic conditions, in particular in regard to water susceptibility, fatigue cracking, dynamic modulus, flow number and low temperature fracture resistance. The results from this first set of experiments showed that this material can perform as well or better than conventional asphalts over a large range of temperatures.